Regional Gray Matter Volume Is Associated with Growth Mindset: A Voxel-Based Morphometry Study. (15th January 2023) - Jia, Xiaoyu; Hao, Lei; He, Li; Li, Ping; Liu, Minglan; Zhang, Yuchi; Qiu, Jiang
Highlights: Growth mindset is individuals' belief about the malleable nature of intelligence. Mindset scores correlate with gray matter volume in the mOFC. No gender difference in the relationship between mindset scores and the mOFC. There is potential neural basis for reward processing underlying growth mindset. Abstract: A growth mindset refers to an individual's beliefs about the malleable nature of intelligence. It plays an important role in motivation and achievement. However, few studies have examined the brain mechanisms involved in the growth mindset. In this study, voxel-based morphometry was used to investigate the relationship between growth mindset and gray matter volume (GMV) in healthy adults' sample from 114 men and 275 women who completed the Growth Mindset Inventory and intelligence test and underwent an anatomical magnetic resonance imaging scan. Whole-brain correlation analyses showed a positive relationship between growth mindset scores and regional GMV of the medial orbitofrontal cortex (mOFC) after controlling for age, sex, and total intracranial volume. This result was robust after controlling for intelligence quotient. The mOFC was primarily related to reward processing, supporting the social-cognitive theory of motivation on growth mindset.